A novel non-linear cumulative fatigue damage model based on the degradation of material memory. (April 2020) - Zhou, Jie; Huang, Hong-Zhong; Barnhart, Miles V; Huang, Guoliang; Li, Yan-Feng
Many fatigue damage models have been investigated based on the S – N curve or modified S – N curve; however, a number of them require additional efforts to determine the material parameters or do not consider the loading history (loading interactions, loading sequences, loading levels, etc.). These limitations can result in extreme deviations for estimating the fatigue life in real-world scenarios. To address these limitations, a new fatigue damage model is developed based on the material memory, which can be described as the degradation of mechanical properties under cyclic loadings. Comparisons with three models are used to demonstrate the validity of the proposed model. Furthermore, four sets of experimental data under two-stress and four-stress levels are carried out to verify the validation of the proposed model, which improves the residual life estimation over the three existing models used for comparison.